Health professionals' perception of maternal health: an ethnography in the Sierra de Totonacapan, Veracruz, Mexico - Niels Michael Dörr (Social Medicine Publication Group, 2021)
Maternal health is a complex issue. In Mexico, especially the population living in poverty and indigenous peoples are affected by health disparities, in particular, demonstrated by skilled birth attendance. The determinants mentioned by health professionals, especially structural barriers, characterize their perception. However, there are other barriers. The concept of intercultural medicine is understood as the adaptation of medical care to local reality to overcome cultural barriers. This article will conclude with a perspective that focuses on the possibilities and limitations of intercultural medicine for maternal health.